Two hegemonies, one island: Cyprus as a “Middle Ground” between the Byzantines and the Arabs (650-850 A.D.) - Zavagno, Luca (Reti Medievali Rivista, 2013)
This paper aims to assess the political and cultural status of the island of Cyprus as the only place within the Mediterranean where Christian heirs of Romans and Muslims shared the local tax revenue to create a buffer zone between two empires. Geographically isolated between the Constantinopolitan and Damascene hegemonies, and marginalized by emperors and caliphs alike, the development of Cyprus was destined to take a unique, perhaps problematic, trajectory. Detailed examination of archaeological material (seals, coins, ceramics and material artifacts) suggests a different interpretative scheme to the one traditionally adopted to interpret the declining fate of Cyprus after the Muslim raids and the occupation of Syria and Palestine. Instead, I propose, Cyprus and its cities were still active from late antiquity to the early middle ages, preserving a variable but still traceable degree of economic vitality (benefitting from the circulation of Byzantine and Arab coinage), which infers the maintenance of complex political, commercial and cultural relations (implicit in issues of imagery and prototypes of coins) between the Byzantine Empire and the Umayyad Caliphate.